Analisis Konsep dan Praktik Ekonomi dari Perspektif Mazhab Maliki - Intan Widuri (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Imam Malik was a great scholar who lived in the 8th century. He is an imam in the Maliki madzab which is one of the four schools of Islamic law. Although his works are not explicitly related to economics, the principles he conveys in the field of law and morals provide a foundation for understanding Islamic economic values. This research will adopt a qualitative approach to deeply understand the economic thought of Imam Malik. This approach involves a thorough literature study of Imam Malik's works, especially in fiqh books that deal with economic aspects. In addition, contextual and historical analysis will be used to place Imam Malik's economic views within his time frame and social situation. Maslahah al mursalah is a concept that prioritizes the element of expediency. One example of the application of the principle of maslahah al mursalah in the determination of Islamic economics in Indonesia is the existence of a sharia economic fatwa issued by the national sharia council of the Indonesian Ulema Council or abbreviated as DSN-MUI. The second concept of Imam Malik's economic thought is the role of government in the economy. Therefore, every policy that contains benefits and benefits for the people, then that is what is planned, implemented, organized, and assessed or evaluated progress. The third thought of Imam Malik is zakat fitrah. According to Imam Malik, the law of zakat fitrah is mandatory. Food issued for zakat fitrah is food that is commonly eaten daily. The dose for zakat fitrah should not be less than one sack (2.4kg or rounded to 2.5kg) even if using the formula one sack equals 4 mud and 1 mud equals 675 g, then 1 sack equals 2.7kg. Zakat fitra paid using cash is makruh. Imam Malik's last economic thought was buying and selling 'inah. According to the Maliki school, buying and selling the 'inah model is not valid because there is an element of sad addhariah, which is the bad purpose of the sale. In buying and selling there is a bad purpose that leads to prohibited actions, which in this case is usury. In MUI's ijtihad, Bay' al 'inah is included in murabahah financing as stated in fatwa DSN NO:04/DSN-MUI/IV/2020 concerning MURABAHAH. There are six decisions listed in the DSN fatwa. The fatwa is also based on verse 275 of Surat al Baqarah, which is one of the legal bases of buying and selling 'inah.